Thoreau’s Spiritual Exercises - Guedes Rossatti, Gabriel (2025)
The goal of this essay is to evaluate the type of philosophy practiced by H. D. Thoreau (1817-1862). After an introduction, part 2 is dedicated to an analysis of P. Hadot’s theses concerning the existence of two different paradigms of philosophy, as well as his notion of “spiritual exercises”. Part 3 investigates Thoreau’s “spiritual exercises” practiced on a daily basis. The conclusion establishes that Thoreau understood philosophy as a concrete transformation of the self, that is, as a way of life.